Distribution extension of anolis Compressicauda Smith & Kerster, 1955 (squamata: dactyloidae) in the state of Tabasco, Mexico - Ríos Rodas, Liliana; Barragán Vázquez, María del Rosario; Torres Pérez, Marco Antonio; Triana Ramírez, Diana Ivette (Instituto de Ecología, A.C., 2017)
Anolis compressicauda has been reported to occur in the Mexican states of Oaxaca, Veracruz and Chiapas. Here we present the first records of this species in the state of Tabasco (Teapa and Tacotalpa municipalities), in the mountainous zone of this state between 100-700 m asl, extending its distributional range 87 km to the north.